Unified Modeling of Discrete Event and Control Systems Applied in Manufacturing - Amanda Arêas de Souza; João José de Assis Rangel (Vértices, 2015)
For the development of both a simulation modeland a control system, it is necessary to build, inadvance, a conceptual model. This is what isusually suggested by the methodologies applied inprojects of this nature. Some conceptual modelingtechniques allow for a better understanding ofthe simulation model, and a clear descriptionof the logic of control systems. Therefore, thispaper aims to present and evaluate conceptuallanguages for unified modeling of models ofdiscrete event simulation and control systemsapplied in manufacturing. The results show thatthe IDEF-SIM language can be applied both insimulation systems and in process control.